Predicting Recurrence after Chronic Subdural Haematoma Drainage. (5th January 2015) - Jack, Andrew; O'Kelly, Cian; McDougall, Cameron; Max Findlay, J.
ABSTRACT: Background: Recurrence of chronic subdural haematomas (CSDHs) after surgical drainage is a significant problem with rates up to 20%. This study focuses on determining factors predictive of haematoma recurrence and presents a scoring system stratifying recurrence risk for individual patients. Methods : Between the years 2005 and 2009, 331 consecutive patients with CSDHs treated with surgery were included in this study. Univariate and multivariate analyses were performed searching for risk factors of increased post-operative haematoma volume and haematoma recurrence requiring repeat drainage. Results: We found a 12% reoperation rate. CSDH septation (seen on computed tomogram scan) was found to be an independent risk factor for recurrence requiring reoperation (p=0.04). Larger post-operative subdural haematoma volume was also significantly associated with requiring a second drainage procedure (p<0.001). Independent risk factors of larger post-operative haematoma volume included septations within a CSDH (p<0.01), increased pre-operative haematoma volume (p<0.01), and a greater amount of parenchymal atrophy (p=0.04). A simple scoring system for quantifying recurrence risk was created and validated based on patient age (< or ≥80 years), haematoma volume (< or ≥160cc), and presence of septations within the subdural collection (yes or no). Conclusion: Septations within CSDHs are associated with larger post-operative residual haematoma collections requiring repeat drainage. When septations are clearly visible within a CSDH, craniotomy might be more suitable as a primary procedure as it allows greater access to a septated subdural collection. Our proposed scoring system combining haematoma volume, age, and presence of septations might be useful in identifying patients at higher risk for recurrence. Abstract : RÉSUMÉ: Prédiction d'une récidive après drainage d'un hématome sous-dural chronique. Contexte: La récidive d'hématomes sous-duraux chroniques (HSDC) après drainage chirurgical est un problème important dont le taux peut s'élever jusqu'à 20%. Cette étude cible les facteurs de prédiction déterminants d'une récidive et présente un système d'évaluation stratifiant le risque de récidive pour des patients particuliers. Méthode: Trois cent trente et un patients consécutifs atteints d'un HSDC, qui ont subi une chirurgie entre 2005 et 2009, ont été inclus dans l'étude. Les données ont fait l'objet d'analyses univariées et multivariées pour rechercher les facteurs de risque d'une augmentation du volume de l'hématome après la chirurgie et d'une récidive de l'hématome nécessitant un nouveau drainage. Résultats: Le taux de réintervention chez nos patients était de 12%. Le cloisonnement de l'HSDC (tel que visualisé à la tomodensitométrie) s'est avéré un facteur de risque indépendant de récidive nécessitant une réintervention (p = 0, 04). Un hématome sous-dural plus considérable en post-opératoire était également associé significativement avec la nécessité d'un second drainage (p<0, 01). Les facteurs de risque d'un hématome plus considérable après la chirurgie étaient le cloisonnement à l'intérieur de l'HSDC (p<0, 01), une augmentation du volume de l'hématome avant la chirurgie (p<0, 01) et une atrophie parenchymateuse plus importante (p<0, 04). Un système de notation simple basé sur l'âge du patient (< ou ≥ 80 ans), le volume de l'hématome (< ou ≥ 160cc) et la présence de cloisons dans l'hématome (oui ou non) pour quantifier le risque de récidive a été créé et validé. Conclusion: Un cloisonnement dans l'HSDC est associé à un hématome résiduel plus considérable en post-opératoire nécessitant un nouveau drainage. Quand des cloisons sont clairement visibles à l'intérieur d'un HSDC, une craniotomie peut être plus appropriée comme première intervention parce qu'elle permet un meilleur accès à tous les segments de l'hématome. Le système de notation que nous proposons, qui combine le volume de l'hématome, l'âge et la présence de cloisonnement, pourrait être utile pour identifier les patients à plus haut risque de récidive.